Poly(NIPAM-co-MPS)-grafted multimodal porous silica nanoparticles as reverse thermoresponsive drug delivery system - Sushilkumar A. Jadhav; Valentina Brunella; Dominique Scalarone; Gloria Berlier (Elsevier, 2017)
Hybrid drug delivery systems (DDS) have been prepared by grafting poly(NIPAM-co-MPS) chains on multimodal porous silica nanoparticles having an inner mesoporous structure and an outer thin layer of micropores. The hybrid thermoresponsive DDS were fully characterized and loaded with a model drug. The in vitro drug release tests are carried out at below and above the lower critical solution temperature (LCST) of the copolymer. The results have revealed that due to the presence of small diameter (~1.3 nm) micropores at the periphery of the particles, the collapsed globules of the thermoresponsive copolymer above its LCST hinders the complete release of the drug which resulted in a reverse thermoresponsive drug release profile by the hybrid DDS.